2015
DOI: 10.3389/fmats.2015.00046
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of C60 on Si(111) 7 × 7 Studied by Supersonic Molecular Beams: Interplay between Precursor Kinetic Energy and Substrate Temperature in Surface Activated Processes

Abstract: Buckminsterfullerene (C 60) is a molecule fully formed of carbon that can be used, owing to its electronic and mechanical properties, as "clean" precursor for the growth of carbonbased materials, ranging from π-conjugated systems (graphenes) to synthesized species, e.g., carbides such as silicon carbide (SiC). To this goal, C 60 cage rupture is the main physical process that triggers material growth. Cage breaking can be obtained either thermally by heating up the substrate to high temperatures (630°C), after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Usually, the terms appearing in the total energy expression are parameterized to reproduce accurately high-level electronic structure calculations for several different bonding conditions. In this way, the transferability of these precalculated terms (the so-called Slater–Koster matrix elements) to different chemical environments and physical conditions as well as a considerable reduction (around 2 orders of magnitude) of the computational cost of this approach with respect to full DFT simulations , are generally obtained. Because of this substantial speed gain, DFTB can be used to simulate systems larger than those accessible by full DFT, to follow their dynamics for longer time scales, and to test how the tuning of the DFTB parameters affects the impact dynamics at an affordable computational cost.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the terms appearing in the total energy expression are parameterized to reproduce accurately high-level electronic structure calculations for several different bonding conditions. In this way, the transferability of these precalculated terms (the so-called Slater–Koster matrix elements) to different chemical environments and physical conditions as well as a considerable reduction (around 2 orders of magnitude) of the computational cost of this approach with respect to full DFT simulations , are generally obtained. Because of this substantial speed gain, DFTB can be used to simulate systems larger than those accessible by full DFT, to follow their dynamics for longer time scales, and to test how the tuning of the DFTB parameters affects the impact dynamics at an affordable computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…From a methodological point of view, approaches beyond molecular dynamics (MD) based on classical force fields have not yet been widely used for studying the impact properties of 2D nanomaterials owing to their high computational cost with increasing size of the system. Notable exceptions have been reported in modeling analogous problems, in which intermediate kinetic energy regimes (around tens of eV) were used to achieve the epitaxial growth of silicon carbide and graphene , via buckyball beams impacting on silicon or metallic substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these scattering problems, it is customary to divide the space into left-hand, center, and right-hand regions, where the former and latter represent the “leads” and the central part is the “device”. Owing to the much lower computational cost of DFTB with respect to other ab initio methods, larger supercells can be used to perform the calculation of charge transport properties. The device region is a 6 × 2 × 1 supercell, having 144 atoms, obtained by using the unit cell lattice vectors computed by Dolgonos et al and optimizing the atomic positions.…”
Section: Computational Methodsmentioning
confidence: 99%
“…In a previous work, concerned with SiC growth induced by SuMBE of C 60 on Si(111), we demonstrated that substrate temperature has very limited effect on cage breaking mechanisms. 43 Thus, we decided to perform DFT simulations at RT. Details on these simulations and the parameters used are given in Section 2.2.1.…”
Section: Born-oppenheimer Dft and Non-adiabatic Molecular Dynamics Si...mentioning
confidence: 99%